Литі елементи модульних будівельних металоконструкцій за моделями, що газифікуються - Шинський, Володимир; Дорошенко, Володимир (Physico-technological Institute of Metals and Alloys, 2023)
The article reviews the common elements of prefabricated modular building metal structures with a list of their advantages and assessment of the prospects for the manufacture of their important components in the LFC process. Such construction with the use of metal structures must have all the prerequisites to become an impetus and an effective solution in the construction industry, which will contribute to the reconstruction of the country. The fabrication of connector assemblies and bolt brackets for connecting beams and connectors with flexible steel plates for seismically unstable conditions is considered. In the department of prof. O.I. Shinsky since 2011 a number of frame-cell thin-walled cast structures have been patented on the basis of models made of expanded polystyrene, which are assembled mainly from repeating elements, and which is similar to the modern method of mounting prefabricated building metal structures. We have also gained experience in casting with LFC parts with cast threads, which simplifies the serial production of ball joints and conical tips for tubular elements. When constructing hangars and warehouses with shell vaults, reducing the weight of metal shells with the obligatory preservation of their required strength is an important requirement for the design of such structures. For this purpose, in particular, the method of inversion of flexible hanging nets formed from a flat state by gravity is used for building structures. The article uses the fact that the inverted chain line serves as an ideal outline for arches and domes, as homogeneous arches in the form of such a line undergo only compression deformation, but not bending. The method of physical modeling of the support surface of the momentless vault shell of a complex curved surface by the method of inversion of the sagging heated thermoplastic synthetic film was developed, which turned out to be simpler than the method of inversion of hanging nets.